The Effect of Teaching Quality and Campus Facilities on Student Learning Motivation - Darman Darman (Eastasouth Institute, 2023)
This study aims to evaluate the effect between teaching quality and campus facilities on student motivation. The quality of teaching and campus facilities is considered as an important factor that can influ-ence student learning motivation. Data was collected through a questionnaire filled out by 93 students from various study programs at Bina Mandiri University, Gorontalo. Statistical analysis was used to examine the influence between these variables. The results showed that there was a significant positive effect between teaching quality and student learning motivation. In addition, campus facili-ties were also found to have a significant influence on student learn-ing motivation.